До характеристики гарантій та юридичної відповідальності територіальних управлінь Державного бюро розслідувань - Богданов, Р. І.; Bohdanov, R. I. (Науковий вісник Київського інституту Національної гвардії України. - 2024. - № 1. - С. 105-109, 2024)
У статті, на основі аналізу наукових поглядів учених та норм законодавства, виокремлено коло юридичних гарантій діяльності територіальних управлінь Державного бюро розслідувань, а також надано їм змістовну характеристику. Наголошено на тому, що юридична відповідальність є одним із тих елементів адміністративно-правового статусу територіального управління, який виконує гарантійну, забезпечувальну роль стосовно ефективності його діяльності.

The article, based on the analysis of the scientific views of scientists and the norms of the current legislation, singles out the circle of legal guarantees of the activities of the territorial offices of the State Bureau of Investigation, and also provides them with a meaningful description. It is emphasized that legal responsibility is one of those elements of the administrative and legal status of territorial administration, which performs a guarantee, ensuring role in relation to the effectiveness of its activities. It is argued that the legal guarantees of the SBI include: 1) guarantees of independence of the SBI from illegal influence: 2) guarantees of reducing corruption risks, including through regulatory and legal regulation of the appropriate level of financial and social security; 3) guarantees of high-quality selection of employees and their further professional development; ) establishment and proper regulation of the factors stimulating the benevolent behavior of the employees of the DBR. It is emphasized that legal responsibility is one of those elements of the administrative and legal status of territorial administration, which performs a guarantee, ensuring role in relation to the effectiveness of its activities. It is appropriate to characterize legal responsibility as coercive measures of a negative nature, based on the norms of criminal, administrative, civil and labor law, which are experienced by employees of territorial administrations when they commit acts that violate their official obligations and cause damage to public and/or private interests. The content of the legal guarantees of the activity of the territorial administrations of the SBI includes: 1) the responsibility of the management of the territorial administration; 2) responsibility of each individual employee. Liability consists of traditional types of legal liability: criminal, administrative, civil and disciplinary. The specificity of the latter is the need to use the general norms of the Law of Ukraine "On Civil Service", which covers disciplinary offenses of all civil servants, while the types of disciplinary penalties and the procedure for their application are determined by the Disciplinary Statute of the National Police of Ukraine.

В статье, на основе анализа научных взглядов ученых и норм законодательства, выделен круг юридических гарантий деятельности территориальных управлений Государственного бюро расследований, а также предоставлена ​​им содержательная характеристика. Отмечено, что юридическая ответственность является одним из тех элементов административно-правового статуса территориального управления, который выполняет гарантийную, обеспечивающую роль относительно эффективности его деятельности.
On the characteristics of guarantees and legal responsibility of the territorial offices of the State Bureau of Investigations
Keywords: гарантії; юридична відповідальність; територіальні управління; Державне бюро розслідувань; guarantees; legal responsibility; territorial administrations; State Bureau of Investigation; гарантии; юридическая ответственность; территориальные управления; Государственное бюро расследований